Dimensions Of Academic Quality In Higher Education In Pakistan - Mumtaz, Humaira (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines the multidimensional aspects of academic quality at Pakistan’s higher education institutions, particularly aiming at the significant roles played by faculty, academic resources, and accreditation. This research intends to get an integrated knowledge that influences national educational quality. A quantitative research approach was used, which involved gathering data from faculty members through a survey tool. Utilizing such an approach made it possible to analyze the data gathered about the perceived quality of higher education institutions. The study applied the purposive sampling technique to draw a representative sample of institutions with diversity in size and types of academic disciplines. Data were evaluated using descriptive statistics and thematic analysis to explore patterns and relationships among the variables. The findings indicate that to enhance academic quality, investment in faculty development programs, improvement of academic infrastructures, and simplification of the accreditation process must be made. Collaboration between higher education institutions and regulatory bodies will provide a single framework for ensuring quality in higher education. This study impacts the existing body of literature by presenting empirical evidence regarding factors influencing academic quality in Pakistani higher education institutions. The findings may be useful for developing strategy-based approaches that focus on strengthening academic standards, improving student outcomes, and enhancing the reputation of Pakistani universities internationally. Keywords: Academic quality, Higher education, Pakistan, Faculty, Academic resources, Accreditation, Quantitative research, Survey, Determinants, Policy implications.